Utilization of GeoGebra Application to Increase Students’ Interest and Result - Silvana Samaray (JUDIMAS, 2020)
This community service workshop aims to develop students' interest in learning mathematics, especially linear programming using GeoGebra Apllication in order to increase their study results. The teaching and learning process are still used conventional method and have not utilized information and communication technology so far. Mathematics learning tends to be considered abstract and difficult to understand. Therefore, many students become less interested in learning it and it affects low study results. The use of information and communication technology-based learning media can be an alternative to improve the quality of the learning process by providing interesting and effective learning. One of them is by utilizing the GeoGebra application in learning process. The workshop was attended by 32 students using a collaborative approach including lecturing, discussion, question and answer, and demonstration methods. The results of the workshop revealed that students showed high interest during the learning process and their scores increased after learning process using the GeoGebra application. Based on the results of the workshop, it can be concluded that the GeoGebra application can be used as learning media in learning mathematics, especially in understanding linear programming because it can develop students’ interest in learning and improve their study results.